Centrosome-centric view of asymmetric stem cell division. Issue 1 (13th January 2021) - Chen, Cuie; Yamashita, Yukiko M.
Abstract : Abstract : The centrosome is a unique organelle: the semi-conservative nature of its duplication generates an inherent asymmetry between 'mother' and 'daughter' centrosomes, which differ in their age. This asymmetry has captivated many cell biologists, but its meaning has remained enigmatic. In the last two decades, many stem cell types have been shown to display stereotypical inheritance of either the mother or daughter centrosome. These observations have led to speculation that the mother and daughter centrosomes bear distinct information, contributing to differential cell fates during asymmetric cell divisions. This review summarizes recent progress and discusses how centrosome asymmetry may promote asymmetric fates during stem cell divisions.